Preparation method of low-viscosity polyether polyol
By using a bimetallic cyanide catalyst prepared by a microchannel reactor in the preparation of polyether polyols, the problems of long induction period, uneven molecular weight distribution and high polyether viscosity in the preparation process of the catalyst in the prior art are solved, and the low viscosity preparation of polyether and more uniform catalyst performance are achieved.
Patent Information
- Application Number
- CN202311241334.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
In the preparation of polyether polyols, existing bimetallic cyanide catalysts have problems such as long induction period, wide molecular weight distribution, high molecular weight tailing phenomenon and high polyether viscosity.
The bimetallic cyanide catalyst is prepared by a microchannel reactor, and the catalyst is prepared by a microchannel reaction method to achieve a more uniform chemical composition, crystalline structure and particle size distribution, thereby reducing the viscosity of the polyether.
In the preparation of polyether, the effect of almost no induction period, the molecular weight distribution is narrow, the high molecular weight tail peak, and the polyether viscosity is low, and the uniformity and reaction efficiency of the catalyst are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyether preparation methods, and in particular to a method for preparing low-viscosity polyether polyol. Background Art
[0002] Polyether polyols, also known as polyoxyolefin polyols, are synthesized by homopolymerization or copolymerization of various compounds containing active hydrogen or amines as initiators with alkylene oxides through ring-opening polymerization. The catalysts used for ring-opening of ethylene oxide / propylene oxide are generally divided into two types: alkaline catalysts or double metal cyanide catalysts. Double metal cyanide catalysts are generally prepared by precipitation reaction of cyanide-free metal salts and metal cyanide. For example, patent CN201510442732.0 uses ZnCl 2 and CoCl 2 The mixed solution and KCo(CN) 6 and KFe(CN) 6 The mixed solution reacts to form two central molecules, which break the lattice structure and improve the catalytic activity. Patent CN201610192925.X uses hydrotalcite as a carrier, polyethylene glycol as a chelating agent, zinc chloride and metal cyanide as precursors, and reacts by dropping an aqueous solution of the central metal into a ligand substance solution. The catalyst has high reaction activity and good product selectivity. Patent CN201980040952.7 adds hydrophobic silica or calcium carbonate to an aqueous solution of potassium cobalt cyanate when preparing the catalyst by precipitation to prepare a supported catalyst, which is easier to separate and filter and is conducive to long-term stable storage.
[0003] However, existing catalysts are all produced and prepared in reactors. Although the precipitation reaction is apparently an instantaneous process, from the perspective of the stirred tank reaction itself, there are distribution gradients in local concentration and temperature, which is not only reflected in the spatial distribution, but also in the temporal distribution. The non-uniformity of the concentration field distribution leads to obvious differences in the distribution of the chemical composition of the obtained catalyst in time and space, while the non-uniformity of the temperature field leads to the simultaneous nucleation and aging reactions of the co-precipitation reaction, resulting in the aggregation and inactivation of active particles, and the inhomogeneity of particle size distribution and crystalline structure. The above reasons make the chemical composition, crystalline structure, and particle size distribution of the catalyst have inhomogeneous polydispersity, resulting in great differences in catalytic activity, which makes it possible to have an obvious induction period when using it to prepare polyethers. During this induction period, the highly active part has triggered a partial reaction but the low-activity part is still in a dormant state. The induction period is often undesirable for actual production. On the one hand, it prolongs the production time (sometimes up to ten hours), and on the other hand, various side reactions are prone to occur during the induction period, affecting the purity of the target product. The end of the induction period is often accompanied by a rapid drop in pressure and a sharp increase in temperature, affecting production safety and stability.
[0004] At the same time, due to the uneven catalytic activity, the molecular weight distribution of the prepared polyether is relatively wide, and even obvious tailing phenomenon occurs at high molecular weight, which makes the polyether have a higher viscosity and affects the application field of the product.
[0005] Therefore, it is of great significance to develop a preparation method that can effectively reduce the viscosity of the prepared polyether and enrich the application field of the polyether. Summary of the invention
[0006] In view of the problems that the double metal cyanide catalyst in the prior art has a long induction period, a wide molecular weight distribution of the prepared polyether polyol, an obvious tailing phenomenon at the high molecular weight, and a high viscosity of the polyether in the process of preparing polyether polyol, the present invention provides a method for preparing a low-viscosity polyether polyol, and uses a double metal cyanide catalyst prepared by a microchannel reactor to achieve the preparation of a low-viscosity polyether. The microchannel reaction method is conducive to the full mixing of the reaction materials, a small concentration gradient, and almost no time difference after the steady state is formed. After the reaction is completed in a very short time, it is removed from the reaction system. The generated particles have a smaller particle size and a more uniform particle size distribution. The obtained catalyst has a more uniform chemical composition, crystalline structure and particle size distribution. There is almost no obvious induction period when preparing polyether, the molecular weight distribution is narrow, there is no high molecular weight tailing peak, and the viscosity of the polyether is low.
[0007] A method for preparing a low-viscosity polyether polyol comprises the following steps: (1) using active hydride as an initiator and double metal cyanide as a catalyst, stirring the initiator and the catalyst, heating and evacuating to obtain a mixture; (2) adding oxidized olefins to the mixture to react; (3) obtaining a crude polyether polyol after the reaction is completed, and removing small molecules from the crude polyether polyol in a stripping tower to obtain a polyether polyol product; wherein the double metal cyanide is prepared by a microchannel reactor.
[0008] The amount of the catalyst is 10-100 ppm of the total amount of the initiator and the olefin oxide, and the mass ratio of the olefin oxide to the initiator is (5-35):1.
[0009] The above-mentioned initiator is an organic compound containing a hydroxyl group.
[0010] Preferably, the initiator is any one of polypropylene oxide triol, glycerol, hydroxypropyl methacrylate, hydroxypropyl acrylate, methallyl alcohol, isopentenol, hydroxyethyl methacrylate, hydroxyethyl acrylate, 3-butyn-1-ol, chloroethanol, and diethylene glycol monovinyl ether.
[0011] The above-mentioned alkylene oxide is selected from at least one of ethylene oxide, propylene oxide or butylene oxide.
[0012] The structure of the double metal cyanide catalyst is shown in the following formula (1):
[0013] L a [M b (CN) c ] d ·xL(H) e yT(1),
[0014] Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ Any of;
[0015] M is selected from any one of Fe, Co, Mn, and Ni ions;
[0016] H is Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 any of carboxylate, nitrate and nitrite ions;
[0017] T is an organic complexing agent, selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octyl alcohol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, and mannitol, preferably one of tert-butanol, n-butanol, and isopropanol.
[0018] The selection of a, b, c, d, and e meets the requirement of positive and negative charge balance; the value range of x is 0.5 to 2; and the value range of y is 1 to 3.
[0019] Preferably, the above L is Zn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ Any of the following, M is Co 3+ , Fe 3+ any one of , H is a chloride ion, and T is any one of tert-butyl alcohol, n-butyl alcohol, and isopropyl alcohol.
[0020] The preparation of the above-mentioned double metal cyanide comprises the following steps: (1) stirring and dissolving a cyanide-free metal salt, a complexing ligand T and deionized water to obtain a solution Sol-A; stirring and dissolving a metal cyanide salt and deionized water to obtain a solution Sol-B; pumping Sol-A and Sol-B into a microchannel reactor at a volume flow ratio of (1-5):1 to react and obtain a dispersion; (2) separating a solid from the dispersion and washing the separated solid with an aqueous solution of the complexing ligand T; (3) drying the solid and crushing it to obtain a catalyst powder.
[0021] In step (2), the solid can be separated from the dispersion by centrifugation or filtration, which can be applied by a vacuum filter, a pressure filter, a filter press, a drum filter or a disc filter. The separated paste is preliminarily washed with an aqueous solution of the complexing ligand T, the preliminarily washing is repeated 1-3 times, and then the complexing ligand T is used for deep washing until the potassium ion content in the filtrate is less than 5 ppm.
[0022] Step (3) is drying at a temperature of usually 20-100° C. under reduced pressure, followed by pulverization to obtain catalyst powder.
[0023] The cyanide-free metal salt for preparing the double metal cyanide catalyst preferably has the general formula (I):
[0024] L(H)e(I)
[0025] in,
[0026] L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ Any one of, preferably Zn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ Any of;
[0027] H is Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 Any of carboxylate, nitrate and nitrite ions, preferably chloride ion;
[0028] When H is sulfate, carbonate or oxalate, e is 1;
[0029] When H is Cl, Br, cyanate, thiocyanate or nitrate, e is 2.
[0030] The metal cyanide salt for preparing the double metal cyanide catalyst preferably has the general formula (II)
[0031] X f M b (CN) c (II)
[0032] in,
[0033] X is selected from one or more metal cations of alkali metals and alkaline earth metals;
[0034] M is selected from any one of Fe, Co, Mn, and Ni ions, preferably Co 3+ , Fe 3+ ; The selection of f, b, and c meets the requirement of positive and negative charge balance;
[0035] The complexing ligand T includes monoalcohols and polyols, and is selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, and mannitol.
[0036] Preferably, the complexing ligand T is any one of tert-butanol, n-butanol and isopropanol.
[0037] The mass concentration of the non-cyanide metal salt in Sol-A is 5-10%, the mass concentration of the complex ligand T is 2-5%; the mass concentration of the metal cyanide salt in Sol-B is 3-5%.
[0038] The inner diameter of the microchannel of the above-mentioned microchannel reactor is 0.10-2.0 mm, the length of the microchannel is 1.0-20 m, and the residence time of the reaction material in the microchannel is 5-25 min (the volume of MCR is 11.781 mL, 1 m is 0.7854 mL).
[0039] The material of the microchannel reactor is selected from stainless steel, alloy, ceramic or carbon silicon glass.
[0040] Since the heat and mass transfer characteristics of the microchannel reactor are orders of magnitude better than those of the traditional kettle reactor, the reaction rate and reaction uniformity are significantly improved, which not only overcomes the problems of long dropwise reaction time and low product yield in the traditional process, but also the prepared double metal cyanide catalyst has a more uniform chemical composition, crystalline structure and particle size distribution. The preparation of double metal cyanide catalysts by microchannel reactors has the advantages of short reaction time, simple process, safe and controllable, flexible adjustment, and continuous operation.
[0041] Compared with the prior art, the present invention has the following advantages: the catalyst obtained by the microchannel reaction method has more uniform chemical composition, crystalline structure and particle size distribution, and there is almost no obvious induction period when preparing polyether. The obtained polyether has a narrow molecular weight distribution, and the molecular weight distribution coefficient D is less than or equal to 1.25; no high molecular weight tailing peak is generated; and the viscosity is low, and the viscosity of the polyether is less than or equal to 3532 mPa·s.
[0042] The entire preparation process of the present invention is simple, controllable, efficient and convenient. The steps used in the reaction are all common operating processes, no special operations or expensive additives are required, the reaction conditions are mild, and the process is green and environmentally friendly. Therefore, it is easy to realize industrial production and has good promotion potential and application value. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The composition of the catalyst was determined by combining elemental analysis with ICP (inductively coupled plasma atomic emission spectroscopy) analysis; the IRIS Advantage full-spectrum direct-reading plasma atomic emission spectrometer was used to determine the Zn and Co content in the catalyst, and the Element Vario EL elemental analyzer was used to determine the C, H, and N elements in the catalyst:
[0045] DMC-1:
[0046] Prepare 1000 g of aqueous solution Sol-A (55 g ZnCl 2 and 25 g tert-butyl alcohol dissolved in 920 g deionized water) and 1000 g 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6 ] dissolved in 965 grams of deionized water), then open two metering pumps, input Sol-A and Sol-B into the spiral MCR system at a speed of 1.25mL / min and 0.50mL / min respectively (the spiral coil is made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1mm on a cylinder with a diameter of 15cm, the total length of the stainless steel hollow tube is 15m, and the residence time is 6.7min), and react with each other and then flow out into a round-bottom flask to obtain a light blue dispersion, which is filtered and separated to obtain a paste, and the paste is filtered under reduced pressure, and the obtained paste is preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol is dissolved in 150 ml of water), and the washing is repeated 3 times and then deep washing is continued with tert-butyl alcohol until the potassium ion content in the filtrate is less than 5ppm, and finally the obtained solid is vacuum dried and crushed to obtain the catalyst powder DMC-1. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 1.25Zn(Cl) 2 2.13TBA.
[0047] DMC-2:
[0048] Prepare 1000 g of aqueous solution Sol-A (53 g ZnCl 2 and 33 g of n-butanol dissolved in 914 g of deionized water) and 1000 g of 3.5% K3 [Fe(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Fe(CN) 6 ] dissolved in 965 grams of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were respectively input into the spiral MCR system at a speed of 2.00 mL / min and 0.80 mL / min (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 4.2 min), and then reacted with each other and flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-2. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Fe(CN) 6 ] 2 1.37Zn(Cl) 2 2.27TBA.
[0049] DMC-3:
[0050] Prepare 1000 g of aqueous solution Sol-A (61 g ZnCl 2 and 35 g of isopropanol dissolved in 904 g of deionized water) and 1000 g of 4.5% K 3 [Fe(CN) 6 ] Aqueous solution Sol-B (45 g K 3 [Fe(CN) 6 ] dissolved in 955 grams of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were respectively input into the spiral MCR system at a speed of 3.72 mL / min and 1.20 mL / min (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 2.4 min), and then reacted with each other and flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-3. Its composition calculated by elemental analysis and ICP determination results is Zn3 [Fe(CN) 6 ] 2 ·1.21Zn(Cl) 2 1.86TBA.
[0051] DMC-4:
[0052] Prepare 1000 g of aqueous solution Sol-A (72 g ZnCl 2 and 41 g of tert-butyl alcohol dissolved in 887 g of deionized water) and 1000 g of 4.2% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (42 g K 3 [Co(CN) 6 ] dissolved in 958 grams of deionized water), then open two metering pumps, input Sol-A and Sol-B into the spiral MCR system at a speed of 2.96mL / min and 0.80mL / min respectively (the spiral coil is made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1mm on a cylinder with a diameter of 15cm, the total length of the stainless steel hollow tube is 15m, and the residence time is 3.1min), and react with each other and then flow out into a round-bottom flask to obtain a light blue dispersion, which is filtered and separated to obtain a paste, and the paste is filtered under reduced pressure, and the obtained paste is preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol is dissolved in 150 ml of water), and the washing is repeated 3 times and then deep washing is continued with tert-butyl alcohol until the potassium ion content in the filtrate is less than 5ppm, and finally the obtained solid is vacuum dried and crushed to obtain the catalyst powder DMC-4. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 ·1.79Zn(Cl) 2 2.86TBA.
[0053] DMC-5:
[0054] Prepare 1000 g of aqueous solution Sol-A (85 g ZnCl 2 and 45 g tert-butyl alcohol dissolved in 870 g deionized water) and 1000 g 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6] dissolved in 965 g of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were fed into the spiral MCR system at a speed of 4.80 mL / min and 1.00 mL / min, respectively (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 2.0 min), and reacted with each other and then flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-5. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 1.98Zn(Cl) 2 1.55TBA.
[0055] DMC-6:
[0056] Prepare 1000 g of aqueous solution Sol-A (93 g ZnCl 2 and 27 g tert-butyl alcohol dissolved in 880 g deionized water) and 1000 g 4.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (45 g K 3 [Co(CN) 6 ] dissolved in 955 grams of deionized water), then open two metering pumps, input Sol-A and Sol-B into the spiral MCR system at a speed of 2.64mL / min and 0.80mL / min respectively (the spiral coil is made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1mm on a cylinder with a diameter of 15cm, the total length of the stainless steel hollow tube is 15m, and the residence time is 3.4min), and react with each other and then flow out into a round-bottom flask to obtain a light blue dispersion, which is filtered and separated to obtain a paste, and the paste is filtered under reduced pressure, and the obtained paste is preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol is dissolved in 150 ml of water), and the washing is repeated 3 times and then deep washing is continued with tert-butyl alcohol until the potassium ion content in the filtrate is less than 5ppm, and finally the obtained solid is vacuum dried and crushed to obtain the catalyst powder DMC-6. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 ·1.01Zn(Cl) 22.05TBA.
[0057] DMC-7:
[0058] Prepare 1000 g of aqueous solution Sol-A (95 g ZnCl 2 and 22 g of isopropanol dissolved in 883 g of deionized water) and 1000 g of 4.6% K 3 [Fe(CN) 6 ] Aqueous solution Sol-B (46 g K 3 [Fe(CN) 6 ] dissolved in 954 g of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were fed into the spiral MCR system at a speed of 1.35 mL / min and 0.50 mL / min, respectively (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 6.4 min), and reacted with each other and then flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-7. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Fe(CN) 6 ] 2 ·1.04Zn(Cl) 2 2.85TBA.
[0059] DMC-8:
[0060] Prepare 1000 g of aqueous solution Sol-A (60 g ZnCl 2 and 35 g tert-butyl alcohol dissolved in 905 g deionized water) and 1000 g 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6] dissolved in 965 grams of deionized water), then open two metering pumps, input Sol-A and Sol-B into the spiral MCR system at a speed of 0.75mL / min and 0.50mL / min respectively (the spiral coil is made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1mm on a cylinder with a diameter of 15cm, the total length of the stainless steel hollow tube is 15m, and the residence time is 9.4min), and react with each other and then flow out into a round-bottom flask to obtain a light blue dispersion, which is filtered and separated to obtain a paste, and filtered under reduced pressure. The obtained paste is preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol is dissolved in 150 ml of water), and then washed three times and then deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate is less than 5ppm. Finally, the obtained solid is vacuum dried and crushed to obtain the catalyst powder DMC-8. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 0.54Zn(Cl) 2 2.80TBA.
[0061] DMC-9:
[0062] Prepare 1000 g of aqueous solution Sol-A (55 g ZnCl 2 and 34 g of isopropanol dissolved in 911 g of deionized water) and 1000 g of 3.8% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (38 g K 3 [Co(CN) 6 ] dissolved in 962 grams of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were respectively input into the spiral MCR system at a speed of 1.52 mL / min and 0.80 mL / min (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 5.1 min), and reacted with each other and then flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-9. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 1.50Zn(Cl) 2·2.00TBA.
[0063] DCM-10
[0064] Prepare 1000 g of aqueous solution Sol-A (55 g ZnCl 2 and 25 g tert-butyl alcohol dissolved in 920 g deionized water) and 1000 g 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6 ] dissolved in 965 grams of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were respectively input into the spiral MCR system at a speed of 2.80 mL / min and 1.00 mL / min (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 3.1 min), and then reacted with each other and flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-10. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 ·1.68Zn(Cl) 2 2.45TBA.
[0065] DMC-11
[0066] Prepare 1000 g of aqueous solution Sol-A (55 g ZnCl 2 and 25 g of isopropanol dissolved in 920 g of deionized water) and 1000 g of 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6] dissolved in 965 grams of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were respectively input into the spiral MCR system at a speed of 2.56 mL / min and 0.80 mL / min (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 3.5 min), and then reacted with each other and flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then continued to be deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-11. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 ·1.57Zn(Cl) 2 2.23TBA.
[0067] DMC-12
[0068] Prepare 1000 g of aqueous solution Sol-A (55 g ZnCl 2 and 25 g of n-butanol dissolved in 920 g of deionized water) and 1000 g of 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6 ] dissolved in 965 grams of deionized water), then two metering pumps were turned on, and Sol-A and Sol-B were respectively input into the spiral MCR system at a speed of 3.52 mL / min and 0.80 mL / min (the spiral coil was made by tightly winding a 316L stainless steel hollow tube with an inner diameter of 1 mm on a cylinder with a diameter of 15 cm, the total length of the stainless steel hollow tube was 15 m, and the residence time was 2.7 min), and then reacted with each other and flowed out into a round-bottom flask to obtain a light blue dispersion, which was filtered and separated to obtain a paste, and the paste was filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and the washing was repeated 3 times and then deep washing was continued with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-12. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 ·1.77Zn(Cl) 22.65TBA.
[0069] DMC-13
[0070] Prepare 1000 g of aqueous solution Sol-A (55 g ZnCl 2 and 25 g tert-butyl alcohol dissolved in 920 g deionized water) and 1000 g 3.5% K 3 [Co(CN) 6 ] Aqueous solution Sol-B (35 g K 3 [Co(CN) 6 ] dissolved in 965 g of deionized water), then Sol-A was slowly added dropwise to Sol-B with a peristaltic pump under rapid stirring, the solution gradually turned milky white, filtered and separated to obtain a paste, filtered under reduced pressure, and the obtained paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water), and then washed deeply with tert-butyl alcohol after repeated washing 3 times until the potassium ion content in the filtrate was less than 5 ppm, and finally the obtained solid was vacuum dried and crushed to obtain the catalyst powder DMC-13. Its composition calculated by elemental analysis and ICP determination results is Zn 3 [Co(CN) 6 ] 2 ·1.13Zn(Cl) 2 2.45TBA.
[0071] The performance parameters of the catalysts DMC-1 to DMC-13 are shown in Table 1 below:
[0072] Table 1
[0073] catalyst <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Catalytic activity (×10 4 g / g)]]> Crystallinity(%) DMC-1 15.1 7.8 7.3 DMC-2 24.5 8.9 9 DMC-3 19.7 8.4 6.1 DMC-4 19.3 8.8 7.4 DMC-5 17.4 8 5.8 DMC-6 18 5 6.2 DMC-7 20.8 6.2 7.6 DMC-8 19.2 9.4 9.8 DMC-9 22.3 5.1 9.7 DMC-10 15.1 9.5 9.9 DMC-11 21.9 8.2 7 DMC-12 18.7 9.5 9.8 DMC-13 6.6 3.2 18.8
[0074] The following Examples 1-13 further disclose experimental data on the catalytic effect of the above-obtained catalyst in ring-opening polymerization reactions using various initiators.
[0075] Application Example 1
[0076] 100 g of polypropylene oxide triol (Mn=450) and 0.022 g of catalyst DMC-1 were added to a 5 L pressure reactor, which was evacuated and heated to 120°C. After adding about 10 g of ethylene oxide, the pressure in the reactor reached 0.2 MPa. The pressure was maintained at 120°C and stirred, and the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then a total of 1011 g of ethylene oxide was added to obtain the product.
[0077] Application Example 2
[0078] 100 g of polypropylene oxide triol (Mn=450) and 0.100 g of catalyst DMC-2 were added to a 5 L pressure reactor, evacuated and heated to 120 ° C. After adding about 10 g of ethylene oxide, the pressure in the reactor reached 0.2 MPa. While maintaining 120 ° C and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 900 grams of ethylene oxide was continuously added to obtain the product.
[0079] Application Example 3
[0080] 100 g of glycerol (M=92.09) and 0.136 g of catalyst DMC-3 were added to a 5 L pressure reactor, evacuated and heated to 120° C. After adding about 7 g of ethylene oxide, the pressure in the reactor reached 0.2 MPa. The pressure was maintained at 120° C. and stirred, and the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 2615 g of ethylene oxide was continuously added to obtain the product.
[0081] Application Example 4
[0082] 100 g of hydroxypropyl methacrylate (M=144.17) and 0.055 g of catalyst DMC-4 were added to a 5 L pressure reactor, evacuated and heated to 120° C. After adding about 5 g of ethylene oxide, the pressure in the reactor reached 0.2 MPa. While maintaining 120° C. and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 2675 g of ethylene oxide was continuously added to obtain the product.
[0083] Application Example 5
[0084] 100 g of hydroxypropyl acrylate (M=130.14) and 0.086 g of catalyst DMC-5 were added to a 5 L pressure reactor, evacuated and heated to 120°C. After adding about 20 g of propylene oxide, the pressure in the reactor reached 0.2 MPa. While maintaining 120°C and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over. Thereafter, 180 g of propylene oxide was continuously added, and a total of 1870 g of ethylene oxide was obtained to obtain the product.
[0085] Application Example 6
[0086] 100 g of methyl allyl alcohol (M = 72.11) and 0.222 g of catalyst DMC-6 were added to a 5 L pressure reactor, evacuated and heated to 120 ° C. After adding about 5 g of ethylene oxide, the pressure in the reactor reached 0.30 MPa. While maintaining 120 ° C and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then ethylene oxide was continuously added in a total of 2674 grams to obtain the product.
[0087] Application Example 7
[0088] 100 g of isopentenol (M=86.13) and 0.058 g of catalyst DMC-7 were added to a 5 L pressure reactor, which was evacuated and heated to 120° C. After adding about 5 g of ethylene oxide, the pressure in the reactor reached 0.30 MPa. The pressure was maintained at 120° C. and stirred, and the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then a total of 2803 g of ethylene oxide was added to obtain the product.
[0089] Application Example 8
[0090] 100 g of hydroxyethyl methacrylate (M=130.14) and 0.046 g of catalyst DMC-8 were added to a 5 L pressure reactor, evacuated and heated to 120° C. After adding about 5 g of ethylene oxide, the reactor pressure reached 0.2 MPa. While maintaining 120° C. and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 2974 g of ethylene oxide was continuously added to obtain the product.
[0091] Application Example 9
[0092] 100 g of hydroxyethyl acrylate (M=116.12) and 0.048 g of catalyst DMC-9 were added to a 5 L pressure reactor, evacuated and heated to 120°C. After adding about 20 g of propylene oxide, the pressure in the reactor reached 0.2 MPa. While maintaining 120°C and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over. Thereafter, 80 g of propylene oxide was continuously added, and a total of 2231 g of ethylene oxide was obtained to obtain the product.
[0093] Application Example 10
[0094] 100 g of 3-butyn-1-ol (M=70.09) and 0.057 g of catalyst DMC-10 were added to a 5 L pressure reactor, which was evacuated and heated to 120° C. After adding about 5 g of ethylene oxide, the pressure in the reactor reached 0.35 MPa. The pressure was maintained at 120° C. and stirred, and the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 2753 g of ethylene oxide was continuously added to obtain the product.
[0095] Application Example 11
[0096] 100 g of chloroethanol (M=80.51) and 0.055 g of catalyst DMC-11 were added to a 5 L pressure reactor, evacuated and heated to 120° C. After adding about 20 g of propylene oxide, the reactor pressure reached 0.2 MPa. The pressure was maintained at 120° C. and stirred, and the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 120 g of propylene oxide was continuously added, and a total of 2512 g of ethylene oxide was obtained to obtain the product.
[0097] Application Example 12
[0098] 100 g of diethylene glycol monovinyl ether (M=132.16) and 0.053 g of catalyst DMC-12 were added to a 5 L pressure reactor, evacuated and heated to 120° C. After adding about 5 g of ethylene oxide, the reactor pressure reached 0.25 MPa. While maintaining 120° C. and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over, and then 2548 g of ethylene oxide was continuously added to obtain the product.
[0099] Comparative Example 1
[0100] 100 g of polypropylene oxide triol (Mn=450) and 0.022 g of catalyst DMC-13 were added to a 5 L pressure reactor, evacuated and heated to 120°C. After adding about 10 g of ethylene oxide, the pressure in the reactor reached 0.2 MPa. While maintaining 120°C and stirring, the pressure change was observed. When the pressure dropped to 0.10 MPa, the induction period was considered to be over. Thereafter, 1011 g of ethylene oxide was continuously added to obtain the product.
[0101] The data recorded in the above experiment are shown in Table 2 below:
[0102] serial number Induction time (min) Reaction rate (g / min) Molecular weight distribution coefficient Polyether viscosity (mPa·s) Application Example 1 17 10.7 1.09 3532 Application Example 2 18 13.7 1.16 2897 Application Example 3 8 15.4 1.10 2258 Application Example 4 11 13.2 1.09 3032 Application Example 5 5 17.8 1.18 2050 Application Example 6 10 16.7 1.08 1864 Application Example 7 16 15 1.08 2441 Application Example 8 8 15.5 1.23 3334 Application Example 9 3 15.7 1.16 2367 Application Example 10 17 16.7 1.18 2085 Application Example 11 20 16.9 1.19 1538 Application Example 12 7 12.6 1.25 2770 Comparative application example 1 180 5.5 1.65 5813
[0103] It can be seen from Table 2 that the polyether polyol product prepared in the present application has good monodispersity and low polyether viscosity (80°C). The DMC catalyst of the present application can be used for the reaction of various initiators with epoxides, including high molecular polymers and various alkali-sensitive hydroxyl-containing small molecules, and can be used not only for the ring opening of propylene oxide, but also for the ring opening of ethylene oxide, with very high catalytic activity, very short induction period or even unobservable, and high reaction rate.
[0104] The DMC-13 catalyst obtained by traditional stirring reaction was applied to comparative application example 1. It can be seen that the induction period of the polymer initiator was significantly longer, reaching 180 minutes, the overall reaction rate was slow, the monodispersity of the product was poor, and the viscosity of the obtained polyether was relatively higher.
[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low-viscosity polyether polyol, characterized in that: The following steps are involved: (1) using active hydride as an initiator and double metal cyanide as a catalyst, stirring the initiator and the catalyst, heating and evacuating to obtain a mixture; (2) adding olefin oxide to the mixture to react; (3) obtaining a crude polyether polyol after the reaction is completed, and the crude polyether polyol is sent to a stripping tower to remove small molecules, Obtaining a polyether polyol product; Wherein, the double metal cyanide is prepared by a microchannel reactor; The preparation of the double metal cyanide comprises the following steps: (1) stirring and dissolving a cyanide-free metal salt, a complexing ligand T and deionized water to obtain a solution Sol-A; stirring and dissolving a metal cyanide salt and deionized water to obtain a solution Sol-B; simultaneously pumping Sol-A and Sol-B into a microchannel reactor for reaction to obtain a dispersion; (2) separating a solid from the dispersion, and washing the separated solid with an aqueous solution of the complexing ligand T; and (3) drying the solid and crushing it to obtain a catalyst powder.
2. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The total volume flow ratio of the Sol-A and Sol-B pumps to the microchannel reactor is (1-5):
1.
3. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The mass concentration of the non-cyanide metal salt in Sol-A is 5-10%, the mass concentration of the complex ligand T is 2-5%; the mass concentration of the metal cyanide salt in Sol-B is 3-5%.
4. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The amount of the catalyst is 10-100 ppm of the total amount of the initiator and the olefin oxide, and the mass ratio of the olefin oxide to the initiator is (5-35):
1.
5. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The initiator is an organic compound containing a hydroxyl group.
6. The method for preparing a low-viscosity polyether polyol according to claim 5, characterized in that: The initiator is any one of polypropylene oxide triol, glycerol, hydroxypropyl methacrylate, hydroxypropyl acrylate, methyl allyl alcohol, isopentenol, hydroxyethyl methacrylate, hydroxyethyl acrylate, 3-butyn-1-ol, chloroethanol, and diethylene glycol monovinyl ether.
7. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The olefin oxide is selected from at least one of ethylene oxide, propylene oxide or butylene oxide.
8. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The double metal cyanide catalyst structure is shown in the following formula (1): 50 a [M b (CN) c ] d ·xL(H) e ·yT(1), Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ Any of; M is selected from any one of Fe, Co, Mn, and Ni ions; H is Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 any of carboxylate, nitrate and nitrite ions; T is an organic complexing agent, selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octyl alcohol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, and mannitol. Any one of tert-butanol, n-butanol, and isopropanol is preferred. The selection of a, b, c, d, and e meets the requirement of positive and negative charge balance; the value range of x is 0.5 to 2; and the value range of y is 1 to 3.
9. The method for preparing a low-viscosity polyether polyol according to claim 8, characterized in that: The L is Zn 2 + , Fe 2+ 、Co 2+ 、Ni 2+ Any of the following, M is Co 3+ , Fe 3+ any one of , H is a chloride ion, and T is any one of tert-butyl alcohol, n-butyl alcohol, and isopropyl alcohol.
10. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The inner diameter of the microchannel of the microchannel reactor is 0.10-2.0 mm, the length of the microchannel is 1.0-20 m, and the residence time of the reaction material in the microchannel is 5-25 min.
11. The method for preparing a low-viscosity polyether polyol according to claim 1, characterized in that: The material of the microchannel reactor is selected from stainless steel, alloy, ceramic or carbon silicon glass.
Citation Information
Patent Citations
Co-precipitation double metal cyanide catalyst, preparation method and application thereof
CN104987502B
Supported double-metal cyanide catalyst and preparation method and application thereof
CN105646866A
Highly Reactive Double Metal Cyanide Compounds
CN112368317B